(untitled) (Web of Teachers: Inderscience Research, 2024)
This article focuses on the derivational aspect of anthroponyms in English, providing examples and analyzing the structural patterns that define them. Among the patterns there have been revealed suffixal, prefixal formations as well as creations based on conversion. By understanding the role of derived anthroponyms, we gain valuable insights into the mechanisms of word formation and the cultural significance of names in the English-speaking world.